Loi et identité féminine dans Jane Eyre. Lecture psychocritique - Max Véga-Ritter (Revue LISA)
This article seeks to throw light on a pattern of undercurrents within Jane Eyre probably originating from the network of relations to the father or (dead) mother figure—or their substitutes—within the closely knit Brontë phratry. It will endeavour to reveal the “son / daughter figure as usurping favourite / and / or / deprived victim” as a hidden “Freudian phantasy” which seems to operate in and organise, Wuthering Heights and some of the Brontës’ Juvenilia as well. A masochistic relationship with the father figure is traced and seen to develop on lines similar to Sigmund Freud’s analysis in “A Child is being beaten”. This study proceeds on to describe the way Jane Eyre gives shape to a new, more feminine sense of authority based on her experience at Lowood and on the moral and spiritual values her identifying with Helen Burns and Miss Temple instilled in her. She builds on them in an effort to stand up to Rochester’s claim to assert his power as a father figure and to bend her to his will until Mason discloses his transgression of Law. By rising to meet Rochester’s challenge, Jane is forced to affirm her own will and her capacity for mastering “her master”. Lucy Snowe in Villette and Shirley Keeldar in Shirley go through a similar experience. Thus Bertha Rochester emerges as the archetype of a feminine power both dreaded and reproved. Far from being Jane’s repressed mirror image, she serves to protect and exonerate her from any charge of resentful anger against Man’s power. Indeed Jane is constantly shown to accommodate a traditional feminine surrender to Love and a firm stand as a Law figure with regard to a masculine partner who uses Law as a means towards the pursuit of Power. Eventually the two characters femininise and / or virilise each other.